2012
DOI: 10.4028/www.scientific.net/amr.565.211
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Chemical Dressing of Coarse Grained Diamond Grinding Wheels

Abstract: This paper deals with a novel dressing method for coarse grained, single layered metal bonded grinding wheels based on the dynamic friction polishing. The diamond friction polishing technique utilizes the thermo-chemical reaction between a diamond sample and a metal tool rotating at high speed. Here, the tips of the diamond grains of a rapidly rotating grinding wheel are thermo-chemically flattened due to the contact with two slowly rotating steel calottes at predetermined friction pressure pd and grinding whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Palmer et al [12] studied the effect of roller dressing on the surface topography, morphology, and characteristics of alumina grinding wheels with different grain shapes, and the study found that very rough grinding wheels are produced at higher feed rates and speed ratios. As reported by Riemer et al [13], the well-dressed electroplated coarse-grained diamond grinding wheel could obtain a ground workpiece surface with surface roughness in the nanometer scale. The truncated diamond abrasive grains with a flat top surface and smaller abrasive protrusion height is meaningful for precision grinding optical glass.…”
Section: Introductionmentioning
confidence: 68%
“…Palmer et al [12] studied the effect of roller dressing on the surface topography, morphology, and characteristics of alumina grinding wheels with different grain shapes, and the study found that very rough grinding wheels are produced at higher feed rates and speed ratios. As reported by Riemer et al [13], the well-dressed electroplated coarse-grained diamond grinding wheel could obtain a ground workpiece surface with surface roughness in the nanometer scale. The truncated diamond abrasive grains with a flat top surface and smaller abrasive protrusion height is meaningful for precision grinding optical glass.…”
Section: Introductionmentioning
confidence: 68%
“…Compared with fine-grained diamond grinding wheels, coarsegrained diamond grinding wheels have significant advantages in terms of grain geometry, grainbond holding strength, and dressing material removal amount, but they also make dressing more difficult. To make the surface of the grinding wheel have smooth coarse-grained diamond grains, Riemer et al [13] proposed a coarse-grained single-layer metal bond grinding wheel dressing method based on the thermochemical reaction between diamond and iron -based materials. The friction and thermochemical effects between the grinding wheel and the dressing block are used to achieve coarse-grained diamond grinding wheel dressing.…”
Section: Introductionmentioning
confidence: 99%